Power in intercommunal knowledge networks: on the endogenous dynamics of network governance and knowledge creation - Holger Straßheim (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2004)
This paper presents empirical and theoretical findings about the endogenous dynamics of interorganisational knowledge networks. Based on a qualitative study of intercommunal knowledge networks in local employment policy a model of knowledge network life cycles is outlined, empirically illustrated, and theoretically explained. It is argued, that the interdependence of knowledge, power and trust plays a central role for the internal dynamics of networks. The paper also aims to show why network innovation and creativity is often closely linked to internal conflicts. The results have consequences for a dynamical concept of network governance. – – Im Mittelpunkt des Papiers stehen empirische und theoretische Befunde zu den endogenen Dynamiken interorganisatorischer Wissensnetzwerke. Die Analyse basiert auf einer qualitativen Studie interkommunaler Wissensnetzwerke der lokalen Beschäftigungspolitik. Dabei wird ein Lebenszyklusmodell interorganisatorischer Wissensnetzwerke skizziert, empirisch illustriert und theoretisch erklärt. In dieser dynamischen Perspektive zeigt sich, dass die Interaktion von Wissen, Macht und Vertrauen für die Entwicklung und Koordination von Wissensnetzwerken eine zentrale Rolle spielt. Zudem wird deutlich, warum Netzwerkinnovationen häufig in Verbindung mit Konfliktereignissen stehen. Die Ergebnisse leisten einen Beitrag zu einem dynamischen Konzept von Netzwerkgovernance.
Keywords: 300